2013
DOI: 10.5229/jkes.2013.16.4.204
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pore-filled Ion-exchange Membranes for Efficient All Vanadium Redox Flow Batteries

Abstract: : Thin pore-filled cation and anion-exchange membranes (PFCEM and PFAEMs, t m = 25-30 µm) were prepared using a porous polymeric substrate for efficient all-vanadium redox flow battery (VRB). The electrochemical and charge-discharge performances of the membranes have been systematically investigated and compared with those of commercially available ion-exchange membranes. The pore-filled membranes were shown to have higher permselectivity as well as lower electrical resistances than those of the commercial mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The VRFB performance of the fabricated PFAEM was compared with the literature known pore-filled ion exchange membrane in Figure . , Most of the reported membranes suffer high vanadium ion diffusion resulting in poor long-term cycling efficiency. Kim et al reported an Engelhard titanosilicate-10 and sulfonated poly­(ether ether ketone) (SPEEK)-filled PTFE substrate for VRFBs.…”
Section: Resultsmentioning
confidence: 99%
“…The VRFB performance of the fabricated PFAEM was compared with the literature known pore-filled ion exchange membrane in Figure . , Most of the reported membranes suffer high vanadium ion diffusion resulting in poor long-term cycling efficiency. Kim et al reported an Engelhard titanosilicate-10 and sulfonated poly­(ether ether ketone) (SPEEK)-filled PTFE substrate for VRFBs.…”
Section: Resultsmentioning
confidence: 99%